Entre religions et spiritualité, quels rôles pour la laïcité dans les collèges publics : une comparaison franco-brésilienne - Gabriela Valente (Éducation et Socialisation)
The rise of studies which take into consideration religiosity and spirituality as a component of rational thought has consequences for the observation of the relationship between the secular and the religious. The objective of this article is to analyze the role of the religious in public schools, in two countries that define themselves as secular, Brazil and France. How are spirituality and religiosity treated in schools? What is the role of the religious in public elementary schools? To answer these questions, an ethnographic study conducted in a comparative education approach gives us access to school situations concerning the religious. The results of this study question two models of secularism in school that give a different place to religiosity in education.